New Fluorescent Dyes as Fluorescent Probes for Examination of Canine Spermatozoa in Cryoprotective Media - Еgorov, M. I.; Dyubko, T. S.; Linnik, T. P.; Belonozhko, A. P.; Еrmolenko, I. G.; Semenova, O. N.; Patsenker, L. D.; Pivovarenko, V. G.; Povrozin, E. A. (Problems of Cryobiology and Cryomedicine, 2006)
Possibilities of using DSM, E-176, 3-DAB, FME fluorescent dyes for examining the effect of cryoprotective agents on canine spermatozoa were studied with the methods of fluorescent spectroscopy and microscopy. FME and 3-DAB dyes were found to be capable of solving the tasks set and DSM, E-176 ones had a limitation due to quite a strong fluorescence of cryoprotectants’ solutions. Studied fluorescent dyes were demonstrated as differently affecting cell motility.